Роль народжуваності у відтворенні населення України - Терець, В.М. (Інститут демографії та соціальних досліджень НАН України, 2010)
У статті досліджено взаємозв’язок між тенденціями народжуваності та процесами відтворення населення України і його старінням, розкрито впливи на сучасний режим відтворення населення з боку чинника народжуваності та безпосередньо пов’язаних із ним факторів. Здійснено порівняльний аналіз динаміки показників народжуваності та узагальнюючих характеристик режиму відтворення населення й індикаторів депопуляції за типом поселення. На основі відповідних розрахунків оцінено вплив факторів інтенсивності режиму відтворення та вікової структури населення на формування природного приросту (убутку) населення в міських поселеннях та сільській місцевості країни протягом останніх п’ятидесяти років. В статье исследована взаимосвязь между тенденциями рождаемости и процессами воспроизводства населения Украины и его старением, раскрыто влияние фактора рождаемости и непосредственно связанных с ним факторов на современный режим воспроизводства населения. Осуществлен сравнительный анализ динамики показателей рождаемости и обобщающих характеристик режима воспроизводства населения, а также индикаторов депопуляции по типу поселения. На основе соответствующих расчетов оценено влияние факторов интенсивности режима воспроизводства и возрастной структуры населения на формирование естественного прироста (убыли) населения в городских поселениях и сельской местности страны за последние пятьдесят лет. The paper is devoted to investigation of the interconnection between trends of fertility and reproduction of population in Ukraine and its aging. The impact factor of fertility and related factors on the regime of reproduction of the population is analyzed in it. The comparative analysis of the dynamics of fertility and the characteristics of population reproduction and indicators of depopulation in urban and rural areas is made. On the basis of the calculations evaluated the effects of the intensity of reproduction ? on the one hand, and the population age structure – on the other hand, on the formation of natural increase (decrease) of population in urban and rural areas of the country over the past fifty years. The influence of modern trends of fertility on the age structure and aging in Ukraine on the future is revealed. The consequences of the modern transformation of fertility and its age-specific rates for the regime of reproduction and depopulation trends in our country in the perspective are evaluated.